(untitled) (Current Horticulture, 2024)
An experiment was conducted to evaluate 37 genotypes of gladiolus for their morphological genetic variation for improvement at the Research Farm of Division of Floriculture and Landscaping, ICAR-Indian Agricultural Research Institute, New Delhi, during 2016-17. There was morphological genetic variability in different cultivars for their different flowering traits. The cultivars, Punjab Glad-2, Praha, Vink’s Glory and Punjab Glance, showed earliness, whereas Malviya Kundan, Malviya Kiran, True Love, Ocilla and Yellow Star were late in flowering. The maximum plant height (122.00, 119.66, 117.66, 114.33 and 113.33 cm) were recorded in Nauvalux, Tiger Flam, Malviya Kiran, Arka Tilak and GS-2 cultivars respectively. The spike and rachis length were also maximum by these cultivars. More number of florets/spike (19.33, 18.33, 17.66 and 17.33) was recorded in Punjab Pink Elegance, Arka Ayush, C.P.G, Tiger Flam and Lady John respectively. All genotypes had a vast morphological genetic diversity.